Penegakan Hukum Terhadap Penyedia Fasilitas Yang Memberikan Peluang Terjadinya Jarimah Maisir - Airi Safrijal; Sahardiani Sahardiani (Fakultas Hukum Universitas Muhammadiyah Aceh, 2018)
Enforcement of jinayat law against organizers and providers of facilities / places that can occur Maisir (gambling) in the city of Banda Aceh is currently not in accordance with applicable regulations as stated in Article 20 of Qanun Number 6 of 2014 on Jinayat Law, namely